Controle da programação de um empreendimento: estudo de caso - Oliveira, Natália Castro de; Mutti, Cristine do Nascimento (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
In the current scenario of crisis in the country, construction companies need to invest in management and in process control. The PPC is one of the most complex processes in companies. This is due to the large number of variables that influence the system and the interdependence between them and external factors. This research was a case study conducted during the execution of a residential building, which had its planning in development and being applied daily. In order to carry out the control in the building site the PPC tool was applied weekly, with daily control. The main problems identified were: unfinished prior task, low productivity, lack of sub contractor´s labor, lack of labor and lack of building materials. Refining the PPC can identify more easily those responsible for delays and take corrective action on site.